Association of Race and Income with Incident Diagnosis of Alzheimer's Disease and Related Dementias among Black and White Older Adults. (May 2023) - Keohane, Laura M.; Nikpay, Sayeh; Braun, Kyle; Cheng, Audrey; Stevenson, David; Buntin, Melinda B.; Yu, Danxia; Blot, William J.; Lipworth, Loren
To investigate how differences in income and education levels may contribute to disparities in incidence of Alzheimer's disease and related dementia (ADRD), we compared ADRD incidence in traditional Medicare claims for 11, 132 Black and 7703 White participants aged 65 and over from a predominantly low-income cohort. We examined whether the relationship between ADRD incidence and race varied by income or education. Based on 2015 incident ADRD diagnoses, Black and White participants had unadjusted incidence rates of 26.5 and 23.2 cases per 1000 person-years, respectively (rate ratio 1.14, 95% CI 1.05–1.25). In multivariable Cox proportional hazard models, the relationship between race and incident ADRD diagnosis did not vary by education level (p-interaction = 0.748) but was modified by income level (p-interaction = 0.007), with higher ADRD incidence among Black participants observed only among higher income groups. These results highlight the importance of understanding how race and economic factors influence ADRD incidence and diagnosis rates.